Discussion on the Improvement Path of Soil Quality in Goaf of Coal Mine - Li, Yanan; Wang, Na (International Journal of Natural Resources and Environmental Studies, 2025)
The large-scale exploitation of coal resources not only supports China's economic and social development, but also causes large-scale coal mine goafs, causing serious soil degradation problems. The degradation of soil quality in goaf is manifested as physical structure destruction, chemical property deterioration and biological function failure, which seriously restricts regional land reclamation and ecological reconstruction. This paper systematically analyzed the core crux of soil quality degradation in coal mine goaf, including soil structure disturbance, nutrient loss, heavy metal pollution and microbial community imbalance. On this basis, from the four dimensions of physics, chemistry, biology and comprehensive integration, the specific path of soil quality improvement is discussed in depth. Finally, the future prospects of constructing the integrated technical system of 'diagnosis-planning-technology integration-monitoring' and improving the policy guarantee and market participation mechanism are put forward, in order to provide theoretical basis and technical support for the ecological environment governance and sustainable development of coal mining areas in China.